THEORETICAL STUDY OF THE USE OF THE POLARIS STAR AS A REFERENCE FOR THE NORTH POINT IN DETERMINING THE QIBLA DIRECTION - Akbar, Reza; Mustaqim, Riza Afrian (Universitas Islam Negeri Ar-Raniry, 2022)
The accuracy of determining the north point is a very important matter in determining the Qibla direction. Finding the north using a compass, especially in buildings, is not encouraged so that an alternative method is needed. Apart from using a compass and istiwa stick (gnomon), Polaris can also be used to reference the north, but it is not popular because of its limited appearance, which is only easily observed in areas which located above latitude 10o N. This study aims to examine theoretically the accuracy of Polaris as a reference for the north point in determining the Qibla direction. This research belongs to library research using secondary data. The data were obtained from various sources such as Stellarium software and various relevant articles. Based on this research, it is concluded that in the region near the equator (less than latitude 10o N), Polaris is difficult to observe because it is very low above the horizon. Thus, for the sake of determining the Qibla direction, the results are inaccurate. Whereas in regions that are located far north from the equator (at latitude above 10o N) the north point can be determined easily because Polaris can be observed quite high. Thus, its use in determining the Qibla direction is classified as accurate.